Fish oil ingestion reduces the number of aberrant crypt foci and adenoma in 1,2-dimethylhydrazine-induced colon cancer in rats - Moreira, A.P.B.; Sabarense, C.M.; Dias, C.M.G.C.; Lunz, W.; Natali, A.J.; Glória, M.B.A.; Peluzio, M.C.G. (Brazilian Journal of Medical and Biological Research, 2009)
We determined the effect of fish oil (FO) ingestion on colonic carcinogenesis in rats. Male Wistar rats received 4 subcutaneous injections (40 mg/kg body weight each) of 1,2-dimethylhydrazine (DMH) at 3-day intervals and were fed a diet containing 18% by weight FO (N = 10) or soybean oil (SO, N = 10) for 36 weeks. At sacrifice, the colon was removed, aberrant crypt foci were counted and the fatty acid profile was determined. Intestinal tumors were removed and classified as adenoma or carcinoma. Liver and feces were collected and analyzed for fatty acid profile. FO reduced the mean (± SEM) number of aberrant crypt foci compared to SO (113.55 ± 6.97 vs 214.60 ± 18.61; P < 0.05) and the incidence of adenoma (FO: 20% vs SO: 100%), but carcinoma occurred equally in FO and SO rats (2 animals per group). The polyunsaturated fatty acid (PUFA) profile of the colon was affected by diet (P < 0.05): total ω-3 (FO: 8.18 ± 0.97 vs SO: 1.71 ± 0.54%) and total ω-6 (FO: 3.83 ± 0.59 vs SO: 10.43 ± 1.28%). The same occurred in the liver (P < 0.05): total ω-3 (FO: 34.41 ± 2.6 vs SO: 6.46 ± 0.59%) and total ω-6 (FO: 8.73 ± 1.37 vs SO: 42.12 ± 2.33%). The PUFA profile of the feces and liver polyamine levels did not differ between groups (P > 0.05). In conclusion, our findings indicate that chronic FO ingestion protected against the DMH-induced preneoplastic colon lesions and adenoma development, but not against carcinoma in rats
Keywords: Colonic aberrant crypt foci; Colorectal cancer prevention; Colorectal tumor; Omega-3 fatty acids; Polyamines